1973
DOI: 10.1136/bmj.4.5888.326
|View full text |Cite
|
Sign up to set email alerts
|

Combined Test for Assessment of Anterior Pituitary Function

Abstract: , Consultant Physician hormone responses (growth hormone, cortisol, LH, FSH, thyroid-stimulating hormone) seen to these stimuli.It is proposed that combined administration of insulin and the hypothalamic releasing hormones may be used as a single test for the assessment of anterior pituitary function. The test is convenient and time saving, and with care can be performed in outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Although there have been many descriptions of individual abnormalities of the HPA system in man (54,62,92,93), few systematic studies of all 3 types of HPA function have been reported in human subjects. We describe here the results of such studies in 158 patients in whom disorders of the HPA system were suspected because of known pituitary tumors or clinical evidence suggesting functional HPA abnormalities.…”
Section: Authors' Studiesmentioning
confidence: 96%
“…Although there have been many descriptions of individual abnormalities of the HPA system in man (54,62,92,93), few systematic studies of all 3 types of HPA function have been reported in human subjects. We describe here the results of such studies in 158 patients in whom disorders of the HPA system were suspected because of known pituitary tumors or clinical evidence suggesting functional HPA abnormalities.…”
Section: Authors' Studiesmentioning
confidence: 96%
“…Other pituitary functions were assessed by a com¬ bined pituitary test (Harsoulis et al 1973), but for this report patients are classified as hypopituitary if given any form of hormone replacement therapy, based on clinical evaluation backed up by low hormone levels. None in the group of 38 patients to be reported was on hormone replacement therapy pre-implant.…”
Section: Follow-up Assessments and Methodsmentioning
confidence: 99%
“…Patients for re-assessment of pituitary function underwent an insulin tolerance test, where there were no contraindications, with simultaneous administration of luteinising hormone/follicle stimulating hormone releasing hormone (LH/FSH-RH) and thyrotrophin releasing hormone (TRH) [12]. In view of the fact that the patients were diabetic and hypopituitary, the dose of insulin given was 0.15 units/kg body weight (Actrapid, Novo).…”
Section: Methodsmentioning
confidence: 99%